Challenges in the implementation of the EAACI AIT guidelines: A situational analysis of current provision of allergen immunotherapy. Issue 4 (12th December 2017) - Ryan, D.; Gerth van Wijk, R.; Angier, E.; Kristiansen, M.; Zaman, H.; Sheikh, A.; Cardona, V.; Vidal, C.; Warner, A.; Agache, I.; Arasi, S.; Fernandez‐Rivas, M.; et al.
Abstract: Purpose: The European Academy of Allergy and Clinical Immunology (EAACI) has produced Guidelines on Allergen Immunotherapy (AIT). We sought to gauge the preparedness of primary care to participate in the delivery of AIT in Europe. Methods: We undertook a mixed‐methods, situational analysis. This involved a purposeful literature search and two surveys: one to primary care clinicians and the other to a wider group of stakeholders across Europe. Results: The 10 papers identified all pointed out gaps or deficiencies in allergy care provision in primary care. The surveys also highlighted similar concerns, particularly in relation to concerns about lack of knowledge, skills, infrastructural weaknesses, reimbursement policies and communication with specialists as barriers to evidence‐based care. Almost all countries (92%) reported the availability of AIT. In spite of that, only 28% and 44% of the countries reported the availability of guidelines for primary care physicians and specialists, respectively. Agreed pathways between specialists and primary care physicians were reported as existing in 32%‐48% of countries. Reimbursement appeared to be an important barrier as AIT was only fully reimbursed in 32% of countries. Additionally, 44% of respondents considered accessibility to AIT and 36% stating patient costs were barriers. Conclusions: Successful working with primary care providers is essential to scaling‐up AIT provision in Europe, but to achieve this, the identified barriers must be overcome. Development of primary care interpretation of guidelines to aid patient selection, establishment of disease management pathways and collaboration with specialist groups are required as a matter of urgency. Abstract :